Activity Test of Anti-Dandruff Shampoo Preparation of Fragrant Pandan Leaf Extract (Pandanus Amaryllifolius Roxb.) Against the fungus Malassezia Furfur - Arini Aprili Pallo; Prisca Deviani Pakan; Desi Indriarini; Magdarita Riwu (Green Publisher Indonesia, 2026)
Dandruff is a scalp disorder caused by Malassezia furfur fungus, often treated with anti-dandruff shampoos. However, synthetic active ingredients in such shampoos may cause side effects like scalp irritation, dryness, or allergies. As an alternative, herbal formulations using fragrant pandan leaves (Pandanus amaryllifolius Roxb.), known for their antifungal properties, can be developed. The objective of this study was to determine and analyze the best Fragrant pandan (Pandanus amaryllifolius Roxb.) leaf extract shampoo formulation and its antifungal activity against Malassezia furfur. The type of research conducted was a true experimental study with a Post-Test Only Control Group Design. In this study, there were treatment groups given a shampoo preparation of fragrant pandanus leaf extract at concentrations of 30%, 50%, and 70%, a negative control group of a shampoo base, and a positive control group of a shampoo containing 1% selenium sulfide under the brand name Selsun. The analysis used was the One-Way ANOVA test. The shampoo preparation of fragrant pandanus leaf extract demonstrated antifungal activity against Malassezia furfur, with inhibition zones obtained at a 30% concentration (15.83 mm), 50% concentration (18.68 mm), 70% concentration (21.89 mm), positive control (21.36 mm), and negative control (0 mm). The 70% Fragrant pandan (Pandanus amaryllifolius Roxb.) leaf extract shampoo preparation is the best formulation because it exhibits optimal physical characteristics and produces the greatest inhibition against Malassezia furfur.